Les cartes d'amor a la novel la grega antiga i al Curial e Güelfa. - MONFERRER, JUAN JOSÉ POMER (Scripta)
The inclusion of love letters in Curial e Güelfa, as well as in the Catalan chivalresque novel, is a literary element whose function is not only confined to the communication between lovers, but also it can activate the plot, cause dramatic reactions and draw the characters' psycological makeup. Novel love letters start with the novel itself, the last genre in ancient Greece, and Curial shows these kind of letters greatly influenced by the works of main Greek novelists.